Characteristics of probability distribution functions of low- and high-latitude current systems during Solar Cycle 24 - Kakad, Bharati; Kakad, Amar (My University, 2019)
Recent solar cycles (SCs) 21–24 have experienced a gradual decrease in their activity with considerable weakening during current SC 24. This is a unique opportunity to examine the long-term response of Earth’s low-latitude ring-current and high latitude auroral elec trojet current systems during such systematically decreasing solar activity. With the advancement in technology, continuous recordings of ground/space magnetic field are available for the last few decades that allow us to explore the behaviour of probability distribution func tions (PDFs) linked with the ring-current and auroral electrojet current systems for past five SCs (20–24). Also, PDFs linked with solar wind parameters that drive these current systems like magnetic field and velocity at Earth’s bow shock are examined. We noticed the significant narrowing of PDF of ring-current and auroral electrojet during SC 24. The number of one-hour intervals with Dst < 150 nT are less than 600 for SCs 20–23, which constitutes less than 0.7% of respective PDF, and number of one-hour intervals with Dst < 250 nT are less than 100 for SCs 20–23, which corresponds to less than 0.1% of respective PDF. But for SC 24 the Dst < 150 nT encountered only for 58 h, which corresponds to 0.06% of PDF and there are no intervals when Dst was < 250 nT. For auroral electrojet, the number of one-hour intervals with AE > 750 nT and AE > 1500 nT are less than 3060 and 70, respectively for SCs 20–23, which corresponds to <4% and <0.06% of respective PDFs. But for SC 24 the AE > 750 nT encountered only for 1398 h, which corresponds to 1.7% of PDF and there are only 9 intervals when AE increased above 1500 nT, which is 0.01% of PDF. It implies that the probability of intense ring-current and auroral electrojet current during SC 24 was unusually low. Such narrow ing is seen in PDFs of the interplanetary magnetic field and solar wind velocity as well. This fair quiet space weather experienced during SC 24 is attributed to the weakening of solar activity, which has subsequently influenced the strength of the interplanetary magnetic field and solar wind velocity at Earth’s bow shock.
Keywords: SOLAR ACTIVITY, Solar cycle 24, Earths magnetosphere, Ring current system, Auroral electrojet current